A new fossil Stempellinella from Eocene Baltic amber, with systematic notes and amendment of the generic diagnosis (Diptera: Chironomidae) - Zakrzewska, Marta; Jankowska, Ariadna (Zootaxa, 2021)
Stempellinella gilkai sp. nov., an Eocene non-biting midge of the subfamily Chironominae, tribe Tanytarsini is described on the basis of the adult male. This is the sixth fossil representative of the genus and the fifth described from Baltic amber ( 40–45 Ma). The species displays a set of morphological characters typical of the genus. To facilitate a delimitation of fossil Stempellinella, a comparison of the most significant characters is provided. The key features of antenna and hypopygium are discussed in detail. A comparative analysis of both extinct and extant Stempellinella representatives allowed to perform an amendment of the current generic diagnosis. Notes on the genus’ palaeoecology and species richness during the Eocene are also included.